Evaluation of Egg Production in Jos North Local Government Area, Plateau State, Nigeria - Haruna, U.; Jibril, S.A.; Kalla, D.J.U.; Suleiman, H. (International Journal of Poultry Science, 2007)
The study was conducted to evaluate small-scale egg production in Jos North Local Government Area of Plateau State. Thirty five (35) poultry farms were purposively selected from the local government area. Structured questionnaire were used to collect data and analyzed using descriptive statistics, farm budgeting model and regression analysis. The results showed that 77.40% of the egg producers were females and 71.43% attended tertiary institutions. The returns per naira invested was found to be 1.35 and the operating ratio was 0.6 indicating the venture was profitable. Regression analysis revealed that the significant variables influencing egg production were feeds (P